Effects of Fuyou Formula on GnRH Secretion and Related Gene Expression in Treating Precocious Puberty - Yi Zhang; Ning Sun; Meng Zhang; Meng Zhang; Qian Ding; Qian Ding; Qian Wang; Yuguang Liang; Huan He; Yuxin Yang; Chunyan Guo; Chunyan Guo (Frontiers Media S.A., 2022)
The Fuyou (Fy) formula is an in-hospital preparation consisting of traditional Chinese medicine (TCM) that has been used for treating precocious puberty (PP) for more than 20 years. In this study, we aimed to clarify the effect of the Fy formula and its major components on PP. To confirm the effect of the Fy formula on the release of hypothalamic gonadotropin-releasing hormone (GnRH), GT1-7 cells were treated with estrogen to build the model group and subsequently treated with the Fy formula and its major components to explore their effects on the secretion of GnRH. The level of GnRH in GT1-7 cells was determined using enzyme-linked immunosorbent assay. The results illustrated that, compared to the model group, the Fy formula inhibited the release of GnRH. In addition, the expression levels of proteins related to GnRH secretion, including GnRH, gonadotropin-releasing hormone receptor (GnRHR), Kiss-1 metastasis-suppressor (Kiss1), G-protein coupled receptor 54 (GPR54), estrogen receptor α (ERα), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor-1 receptor (IGF-1R), were detected by real-time polymerase chain reaction (RT-qPCR). The results demonstrated that the Fy formula significantly reduced the level of GnRH secretion in the GT1-7 cell lines compared with the model group. Moreover, it significantly downregulated the expression of GnRH, GnRHR, Kiss1, GPR54, ERα, IGF-1, and IGF-1R. In summary, our results indicate that the Fy formula and its major components may inhibit the effects of estrogen, which alleviates PP through transcriptional regulation of target genes.